Failure mechanisms and mechanical behavior of wedge-containing tunnel roof rock mass under biaxial loading - Ruiyang Bi; Chaoshui Xu; Minghui Liu; Kun Du (International Journal of Mining Science and Technology)
The stability of underground tunnel roofs is strongly influenced by wedge blocks formed by complex joint networks. The mechanical behavior and failure mechanisms of different roof wedge blocks in arched holes were investigated under biaxial stress conditions. The crack evolution and failure modes of the specimens were analyzed through acoustic emission (AE), digital image correlation (DIC), and discrete element method (DEM). Results show significant variations in mechanical properties: specimens T1 (extremely unstable triangular) and T2 (extremely unstable quadrilateral) exhibited higher strength than T3 (extremely stable triangular) and T4 (extremely stable quadrilateral), while support more effectively enhanced the strength of T3 and T4. Failure modes were classified as rock-dominated, wedge-dominated, or co-dominated. Cracks typically initiated near the wedge and propagated outward. Unsupported specimens developed tensile cracks at the hole bottom, shear cracks at the sides, and mixed cracks along wedge boundaries, whereas supported specimens mainly exhibited cracks at the roof and sides. Stress analysis indicated that unsupported conditions induced high stress differences, promoting localized shear failure. Wedge geometry significantly affected shear stress redistribution at the roof. These findings highlight the critical role of support and wedge block geometry in controlling stress distribution and failure mechanisms in arched tunnels.